The impact of antimicrobial stewardship program implementation at four tertiary private hospitals: results of a five-years pre-post analysis - Al-Omari, Awad; Al Mutair, Abbas; Alhumaid, Saad; Salih, Samer; Alanazi, Ahmed; Albarsan, Hesham; Abourayan, Maha; Al Subaie, Maha (Antimicrobial resistance & infection control, 2020)
Background Antimicrobial stewardship (AMS) programs have shown to reduce the emergence of antimicrobial resistance (AMR) and health-care-associated infections (HAIs), and save health-care costs associated with an inappropriate antimicrobial use. The primary objective of this study was to compare the consumption and cost of antimicrobial agents using defined daily dose (DDD) and direct cost of antibiotics before and after the AMS program implementation. Secondary objective was to determine the rate of HAIs [ Clostridium difficile ( C. difficile ), ventilator-associated pneumonia (VAP), and central line-associated bloodstream infection (CLABSI) before and after the AMS program implementation. Methods This is a pre-post quasi-experimental study. Adult inpatients were enrolled in a prospective fashion under the active AMS arm and compared with historical inpatients who were admitted to the same units before the AMS implementation. Study was conducted at four tertiary private hospitals located in two cities in Saudi Arabia. Adult inpatients were enrolled under the pre- AMS arm and post- AMS arm if they were on any of the ten selected restricted broad-spectrum antibiotics (imipenem/cilastatin, piperacillin/tazobactam, colistin, tigecycline, cefepime, meropenem, ciprofloxacin, moxifloxacin, teicoplanin and linezolid). Results A total of 409,403 subjects were recruited, 79,369 in the pre- AMS control and 330,034 in the post- AMS arm. Average DDDs consumption of all targeted broad-spectrum antimicrobials from January 2016 to June 2019 post- AMS launch was lower than the DDDs use of these agents pre- AMS (233 vs 320 DDDs per 1000 patient-days, p = 0.689). Antimicrobial expenditures decreased by 28.45% in the first year of the program and remained relatively stable in subsequent years, with overall cumulative cost savings estimated at S.R. 6,286,929 and negligible expenses of S.R. 505,115 ( p = 0.648). Rates of healthcare associated infections involving C. difficile , VAP, and CLABSI all decreased significantly after AMS implementation (incidence of HAIs in 2015 compared to 2019: for C. difficile , 94 vs 13, p = 0.024; for VAP, 24 vs 6, p = 0.001; for CLABSI, 17 vs 1, p = 0.000; respectively). Conclusion Implementation of AMS program at HMG healthcare facilities resulted in reduced antimicrobials use and cost, and lowered incidence of healthcare associated infections.